Frankly, my dear : Gone with the wind revisited - Haskell, Molly (Icons of America., 2009)
How and why has the saga of Scarlett O'Hara kept such a tenacious hold on our national imagination for almost three-quarters of a century? In the first book ever to deal simultaneously with Margaret Mitchell's beloved novel and David Selznick's spectacula.